PENGELOLAAN RECORDS CENTER DI KANTOR ARSIP DAN PERPUSTAKAAN DAERAH KABUPATEN KLATEN - , UCI TRI RAHMAWATI; , Waluyo, S.S, M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study reports describes the Managing of Records Center in Kantor Arsip dan Perpustakaan Daerah Kabupaten Klaten. The first step begin from survey or review the location. To see how the inactive records management and managing records center, then observe the condition of the existing records and records center observe conditions such as infrastructure, spatial layout, and records center environment. This research used three different data collection methods. First method is interview, the interview was conducted with involvement of resource persons who are considered to have enough information to complete this final report. In addition there are observation method, the observation here is intended to looking directly the condition or record and the managing records center. Last method is the most basic method of the research conducted. Furthermore , there is literature review, which the literature data obtained from existing references such as, books, legislation, internet, booklets and others. The result of this research showed that Kantor Arsip dan Perpustakaan Daerah Kabupaten Klaten still not maximized in the managing records center, it can be seen from some results of the method data collection conducted during the research. In addition the problems encountered is the lacking of adequate space to the records volume.